2010
DOI: 10.1111/j.1440-1746.2010.06300.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower prevalence of hypercholesterolemia and hyperglyceridemia found in subjects with seropositivity for both Hepatitis B and C strains independently

Abstract: This large scale community-based study demonstrated that subjects with seropositivity for Hepatitis C not only had lower prevalence of hypercholesterolemia and hypertriglyceridemia but subjects with seropositivity for Hepatitis B had the same trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 36 publications
(83 reference statements)
5
50
1
Order By: Relevance
“…Chronic HBV infection is associated with lower prevalence of hypertriglyceridemia in men and women (Jan et al 2006;Chen et al 2010;Wong et al 2012;Chung et al 2014;Huang et al 2016). In this study, however, OBI was detected at higher frequency in HLP patients than in replacement blood donor population controls (9.5% vs. 2.4%, P < 0.001), which suggested a positive association between OBI and HLP.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Chronic HBV infection is associated with lower prevalence of hypertriglyceridemia in men and women (Jan et al 2006;Chen et al 2010;Wong et al 2012;Chung et al 2014;Huang et al 2016). In this study, however, OBI was detected at higher frequency in HLP patients than in replacement blood donor population controls (9.5% vs. 2.4%, P < 0.001), which suggested a positive association between OBI and HLP.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies showed that chronic hepatitis B virus (HBV) infection was associated with lower prevalence of hypertriglyceridemia (Jan et al 2006;Chen et al 2010;Wong et al 2012;Chung et al 2014;Huang et al 2016) or hypercholesterolemia (Chen et al 2010;Liu et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In other words, whether these studies [3641, 4447] meet the MetS criteria (Q4: The MetS and its components were defined accurately) did not affect the statistical results (SMD), so they were labeled with “UR” (unrelated) for Q4 in Table 3. The remaining 20 studies [1017, 2635, 42, 43] reported ORs or crude data for calculating the ORs. The MetS criteria used in these 20 studies was similar, but not identical.…”
Section: Resultsmentioning
confidence: 99%
“…For “Elevated TG”, the pooled OR was from 14 studies [1016, 26, 28, 30, 31, 3335], and the SMD was from 14 studies [10, 16, 17, 26, 31, 34, 36, 37, 39, 42, 4447]. They are not identical.…”
Section: Resultsmentioning
confidence: 99%
“…Generally the redox species in the iodide/tri-iodide solution ensure holes enable transport from the oxidized dye to the counter electrode to close the redox cycle. However with a cracked film the conducting substrate intended to come into contact with oxidizing species in the electrolyte which enhance the recombination probability and in turn reduce the efficiency of the solar cell [14]. Conversely, the cracks connection will promote the formation of large dense domains which favor light scattering and harvesting.…”
Section: Protocol )mentioning
confidence: 99%